Daya Saing UMKM Untuk Mengikuti Pengadaan Barang dan Jasa Pemerintah di Kabupaten Hulu Sungai Utara - Haris Fadillah; Hairudinor Hairudinor (Universitas Lambung Mangkurat, 2022)
ABSTRACT This study aims to determine the competitiveness of UMKM to follow procurement of goods and government services and supporting factors and hinder the competitiveness UMKM to follow procurement of goods and government services in Hulu Sungai Utara District. This research is qualitative research and was conducted on Electronic Procerument Services (LPSE) and UMKM to follow procurement of goods and government services. The increase in market share and the increase in profits in last three years decreased due to many competitors and the packages is getting smaller because the government for the procurement of goods and government services. Besides that, supporting factors are having an understanding of procurement of goods and government services, working partners, procurement of goods and government services specification, and promotion. The obstacle factors are lack of experts and IT personnel, capital, increasing competitors, lack of experience and here is still a syndication between the UMKM with authorized government official. The government support the specification program for the procurement of goods and services to be disseminated to UMKM workers involved in the procurement of goods and government services, increase IT personnel so that every time there is an offer or information related to the procurement of goods and government services, they are always responsive. Every UMKM need to work together with experts so thatlater it will be easier to procure goods and government services, need to think about capital and be fair and not easily influenced by syndications between UMKM workers or concerned government officials. Keywords: Competitiveness, UMKM and Procurement of goods and government services